Designing Effective Entrepreneurship Education Programs To Cultivate Long-Term Entrepreneurial Mindsets In Generation Z - Nuralam, Inggang Perwangsa; Aini, Edlyn Khurotul; Ruwaida, Hifni Bahiroh; Anapah, Maria Goreti Ilmiana (Universitas Pamulang, 2025)
The increase in entrepreneurial activity among Generation Z shows excellent potential to drive innovation and economic growth, but there remains a gap between long-term entrepreneurial intentions and behavior. Entrepreneurship education often fails to foster sustainable entrepreneurial passion because of its theoretical, less contextual approach. This study aims to analyse the influence of entrepreneurship education on entrepreneurial passion, identify the most effective types of programs, and formulate institutional strategies in designing sustainable entrepreneurship education for Generation Z. Using a Systematic Literature Review approach following the PRISMA protocol, this study selected 27 of 1,458 articles obtained through the Scopus database (2024–2025, English language, open access). The results of the thematic analysis show four main findings: (1) experiential learning effectively fosters passion through project-based learning; (2) integration of digital technology increases student relevance and engagement; (3) social support and the campus ecosystem strengthen sustainable entrepreneurial behavior; and (4) social value-based learning forms authentic passion. Effective entrepreneurship education for Generation Z needs to be oriented towards real experiences, social values, and digital technology.